2009
DOI: 10.3390/ijms10031226
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathological Role of Alpha-synuclein in Parkinson’s Disease Through Iron Mediated Oxidative Stress; The Role of a Putative Iron-responsive Element

Abstract: Abstract:Parkinson's disease (PD) is the second most common progressive neurodegenerative disorder after Alzheimer's disease (AD) and represents a large health burden to society. Genetic and oxidative risk factors have been proposed as possible causes, but their relative contribution remains unclear. Dysfunction of alpha-synuclein (α-syn) has been associated with PD due to its increased presence, together with iron, in Lewy bodies. Brain oxidative damage caused by iron may be partly mediated by α-syn oligomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 199 publications
(239 reference statements)
6
71
0
Order By: Relevance
“…We also studied the ability of FMRP and TDP-43 to regulate their own expression levels through autogenous interactions, characterizing their binding sites in great detail (Schaeffer et al 2001;Ayala et al 2011). We analyzed the interaction between IRP-1 and APP (Cho et al 2010) and predicted the interaction between IRP-1 and an IRE-like region of α-synuclein mRNA, which represents a link to the iron-pathway deregulation associated with PD (Olivares et al 2009). Finally, we investigated the ability of RNA aptamers to bind to aggregation-prone regions of prions (Proske et al 2002), which shows that our theoretical framework could be useful for the in silico screening of RNA-based therapeuticals (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also studied the ability of FMRP and TDP-43 to regulate their own expression levels through autogenous interactions, characterizing their binding sites in great detail (Schaeffer et al 2001;Ayala et al 2011). We analyzed the interaction between IRP-1 and APP (Cho et al 2010) and predicted the interaction between IRP-1 and an IRE-like region of α-synuclein mRNA, which represents a link to the iron-pathway deregulation associated with PD (Olivares et al 2009). Finally, we investigated the ability of RNA aptamers to bind to aggregation-prone regions of prions (Proske et al 2002), which shows that our theoretical framework could be useful for the in silico screening of RNA-based therapeuticals (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…7; Olivares et al 2009). According to our calculations, the IRE-containing fragment of α-synuclein mRNA (nucleotides 190-252) has the highest propensity to bind to IRP-1 ( Fig.…”
Section: Iron-mediated Expression Of App and α-Synucleinmentioning
confidence: 99%
“…Evidence from studies on inherited disorders of iron metabolism indicates that neurodegeneration occurs with iron accumulation (Mills et al, 2010). Olivares et al, (2009) reported that iron accumulation is probably a primary event and not a consequence of degenerative diseases. In a rat model, when FeCl 3 was injected into the substantia nigra, there was selective decrease in striatal dopamine suggesting that iron is responsible for dopaminergic neurodegeneration.…”
Section: Iron Ros and Neurodegenerationmentioning
confidence: 99%
“…In mice, deletion of the gene encoding for IRP2 which interferes with regulation of iron metabolism has been found to result in abnormal iron deposition in the brain, as well as ataxia, tremors and neurodegeneration. Similarly mutation in the gene coding for a ferritin subunit and polymorphisms in genes related to iron homeostasis have been associated with iron deposits, neuronal degradation and sometimes PD (Olivares et al, 2009). …”
Section: Iron Ros and Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation